The C-terminus of Apc does not influence intestinal adenoma development or progression - Lewis, A; Davis, H; Deheragoda, M; Pollard, P; Nye, E; Jeffery, R; Segditsas, S; East, P; Poulsom, R; Stamp, G; Wright, N; Tomlinson, I (2012)
Adenomatous polyposis coli (APC) mutations are found in most colorectal tumours. These mutations are almost always protein-truncating, deleting both central domains that regulate Wnt signalling and C-terminal domains that interact with the cytoskeleton. The importance of Wnt dysregulation for colorectal tumourigenesis is well characterized. It is, however, unclear whether loss of C-terminal functions contributes to tumourigenesis, although this protein region has been implicated in cellular processes-including polarity, migration, mitosis, and chromosomal instability (CIN)-that have been postulated as critical for the development and progression of intestinal tumours. Since almost all APC mutations in human patients disrupt both central and C-terminal regions, we created a mouse model to test the role of the C-terminus of APC in intestinal tumourigenesis. This mouse (Apc ΔSAMP) carries an internal deletion within Apc that dysregulates Wnt by removing the beta-catenin-binding and SAMP repeats, but leaves the C-terminus intact. We compared Apc ΔSAMP mice with Apc 1322T animals. The latter allele represented the most commonly found human APC mutation and was identical to Apc ΔSAMP except for absence of the entire C-terminus. Apc ΔSAMP mice developed numerous intestinal adenomas indistinguishable in number, location, and dysplasia from those seen in Apc 1322T mice. No carcinomas were found in Apc ΔSAMP or Apc 1322T animals. While similar disruption of the Wnt signalling pathway was observed in tumours from both mice, no evidence of differential C-terminus functions (such as cell migration, CIN, or localization of APC and EB1) was seen. We conclude that the C-terminus of APC does not influence intestinal adenoma development or progression. Copyright © 2011 Pathological Society of Great Britain and Ireland. Published by John Wiley and Sons, Ltd.